2017
DOI: 10.14257/ijt.2017.5.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Design Exceptions on Highway Safety

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other research has compared the safety performance of locations with SSD design exceptions with that of locations that meet minimum SSD criteria (25)(26)(27). The design exceptions related to SSD in these papers ranged from 65 of 562 (27), four of 61 exceptions (25), and an unspecified percentage (26). The research articles on design exceptions all indicated that there were no differences in safety performance for crash rate, crash frequency, or crash severity between locations that meet and that do not meet minimum SSD criteria.…”
Section: Safety Impacts Of Ssdmentioning
confidence: 99%
“…Other research has compared the safety performance of locations with SSD design exceptions with that of locations that meet minimum SSD criteria (25)(26)(27). The design exceptions related to SSD in these papers ranged from 65 of 562 (27), four of 61 exceptions (25), and an unspecified percentage (26). The research articles on design exceptions all indicated that there were no differences in safety performance for crash rate, crash frequency, or crash severity between locations that meet and that do not meet minimum SSD criteria.…”
Section: Safety Impacts Of Ssdmentioning
confidence: 99%
“…In VSNs, emergence messages have to be disseminated without any time delay to avoid potential accidents [13][14][15][16][17][18][19][20]. If some neighbor vehicles don't receive the emergency message because of message collision or transmission error [21], they may be exposed to secondary accidents. To resolve these problems, many research works are proposed in VANETs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%